Polymorphism −116 C / G of Human X ‐box‐Binding Protein 1 Promoter is Associated with Risk of A lzheimer's Disease - Liu, Sheng‐Yuan; Wang, Wei; Cai, Zhi‐You; Yao, Li‐Fen; Chen, Zhong‐Wei; Wang, Chang‐Yi; Zhao, Bin; Li, Ke‐Shen (CNS neuroscience & therapeutics, 2013)
AimAlzheimer's disease (AD) is a multifactor disease that has been reported to have a close association with endoplasmic reticulum (ER) stress response. In the response, the regulator factor human X‐box‐binding protein 1 (XBP1) has been shown to facilitate the refolding and degradation of misfolded proteins, prevent neurotoxicity of amyloid‐beta (Aβ) and tau, and play an important role in the survival of neurons. The aim in the study was to analyze the potential association between the −116C/G polymorphism of XBP1 and the risk of AD.MethodsThe association between −116C/G polymorphism of XBP1 promoter and possible risk of AD was assessed among 276 patients with AD and 254 matched healthy individuals in a case–control study.ResultsOverall, there was a significantly statistical difference in genotype (P = 0.0354) and allele frequencies (P = 0.0150, OR = 1.3642, 95% CI = 1.0618–1.7528) between the AD subjects and control subjects, showing that the −116C/G polymorphism of XBP1 might lead to increased susceptibility for AD in a Chinese Han population. In addition, the −116CG and −116GG genotypes were significantly associated with increased AD risk in female (P = 0.0217) and in subjects with APOE є4 (−) (P = 0.0070) in stratified analyses, and the −116CC genotype was significantly associated with fast cognitive deterioration in the AD patients (P = 0.0270).ConclusionThe study supports a role for the −116C/G polymorphism of XBP1 gene in the pathogenesis of AD, and further studies with a larger sample size and detailed data should be performed in other populations.